VOLATILE COMPOUNDS OF WATER-ETHANOLIC EXTRACT OF SATUREJA MONTANA L. - A. E. Paliy; L. A. Khlypenko (Фармация и фармакология (Пятигорск))
We have studied a composition and content of volatile compounds of Satureja montana L. extract. It was established that concentration of volatile compounds in water-ethanol extract of S. montana amounted to 325 mg/100g. The principal component of the extract is carvacrol. It was shown that the extract of Satureja montana represents high biological value